Real-World Response and Outcomes in Patients With NSCLC With EGFR Exon 20 Insertion Mutations - Sai-Hong Ignatius Ou, MD; Huamao M. Lin, PhD, MBA; Jin-Liern Hong, PhD; Yu Yin, MS, MPH; Shu Jin, MS; Jianchang Lin, PhD; Minal Mehta, MBBS; Danny Nguyen, MD; Joel W. Neal, MD, PhD (JTO Clinical and Research Reports, 2023)
Introduction: This study describes treatment patterns and outcomes in patients with NSCLC with EGFR exon 20 insertions (EGFRex20ins) in the United States. Methods: The Flatiron Health electronic health record database was used to select three cohorts among patients diagnosed with NSCLC with EGFRex20ins (January 1, 2011–February 29, 2020): (1) first-line (1L) or patients receiving 1L therapy after documented EGFRex20ins; (2) second or later-line (≥2L) or patients receiving ≥2L therapy after documented EGFRex20ins; and (3) ≥2L postplatinum trial-aligned, or ≥2L patients previously treated with platinum chemotherapy whose baseline characteristics aligned with key eligibility criteria (initiating new treatment after documented EGFRex20ins and ≥1 previous treatment excluding mobocertinib or amivantamab) of the mobocertinib trial NCT02716116. Real-world end points were confirmed overall response rate, overall survival, and progression-free survival. Results: Of 237 patients with EGFRex20ins-mutated NSCLC, 129 and 114 patients were included in the 1L and ≥2L cohorts, respectively. In 1L patients, platinum chemotherapy plus nonplatinum chemotherapy (31.0%) and EGFR tyrosine kinase inhibitors (28.7%) were the most common regimens. In ≥2L patients, immuno-oncology monotherapy (28.1%) and EGFR tyrosine kinase inhibitors (17.5%) were the most common index treatments. For any 1L, ≥2L, and ≥2L postplatinum trial-aligned patients, the confirmed overall response rate was 18.6%, 9.6%, and 14.0%, respectively; the median overall survival was 17.0, 13.6, and 11.5 months; the median progression-free survival was 5.2, 3.7, and 3.3 months, respectively. Conclusions: The outcomes for patients with NSCLC with EGFRex20ins were poor. This real-world study provides a benchmark on treatment outcomes in this patient population and highlights the unmet need for improved therapeutic options.